FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTIHAN PADA REMAJA PUTRI DI SMAN 11 PEKANBARU TAHUN 2018 - Novita Lusiana (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Abstract: Data on research on women's health research shows that 75% of women in the world must have vaginal discharge at least ever lived and 45% can experience it twice or more. Such conditions can be prevented by carrying out good vulva hygiene habits, while this habit must be a problem that must be accustomed to each individual and is needed with knowledge, for which health workers have an important role to educate the public about the importance of good health to be maintained. This study uses a type of quantitative analytic research with the research design used is cross sectional. The subjects of this study were 64 female students of class XI and 58 female students of class XII at SMAN 11 Pekanbaru for the period 2017-2018. Data collection is done by filling out the questionnaire. Data analysis was performed using the Chi Squere test. The incidence of vaginal discharge at SMAN 11 Pekanbaru is quite high, namely 56.6% of respondents consider vaginal discharge. Regarding the knowledge of vaginal discharge with a value (P = 0.05), not related to the assessment of vaginal discharge at the value (P = 0.056) and not related to personal hygiene about how to use vaginal discharge on students with a value (P = 0.542). There is a significant relationship between Knowledge of Leucorrhoea in Young Women at SMAN 11 Pekanbaru in 2018. The program that is very effective in increasing young women's knowledge about vaginal discharge is to collaborate with Puskesmas and health workers in general. This knowledge will increase. Keywords: Knowledge, Attitude, Personal Hygine, Leucorrhoea